Study of long-acting vs daily growth hormone: peak levels, AUC, action duration, and IGF-1 - Ashraf Soliman; Fawzia Alyafei; Nada Alaaraj; Noor Hamed; Shayma Mohamed; Ahmed Elawwa; Vincenzo De Sanctis (Academia Biology)
Introduction: Long-acting growth hormone (LAGH) therapy was developed to improve adherence by reducing injection frequency compared to daily growth hormone (GH) therapy. Objectives: This review assesses the impact of LAGH therapy on serum levels of GH and insulin-like growth factor-1 (IGF-1) and evaluates the potential metabolic and safety risks compared to the natural pulsatile secretion of GH and daily GH injections in normal children. Methods: A comprehensive literature search identified studies examining the effects of LAGH therapy on serum GH and IGF-1 levels. Results: Studies from 2010 to 2024 were included. LAGH formulations maintain elevated IGF-1 levels for extended periods, in contrast to the episodic peaks and troughs of natural GH secretion. These formulations demonstrate efficacy in promoting growth and maintaining IGF-1 levels but are associated with sustained nonpulsatile GH exposure. Significant intra- and interindividual variability in GH uptake after injection has been observed, with higher GH concentrations correlating with increased IGF-1 levels and growth response. Concerns have been raised about adverse metabolic outcomes, including decreased insulin sensitivity. Sustained high IGF-1 levels with LAGH therapy may also increase risks for certain cancers and proliferative disorders, although evidence remains inconclusive. Discussion: While LAGH therapy offers improved adherence, it leads to nonphysiological, sustained high levels of GH and IGF-1, raising concerns about long-term metabolic effects. Conclusions: LAGH therapy presents a viable alternative to daily GH injections, providing improved adherence and convenience. However, continuous monitoring of long-term metabolic and safety risks and performing long-term studies are crucial to ensuring safe and effective use in clinical practice.